The variation of conceptions on the nature of science: a phenomenographic study on science learners from multiple educational tiers / Jasmine Jain - Jain, Jasmine (Institute of Graduate Studies, UiTM, 2014)
The study was grounded in the goal of science education to produce individuals who are scientifically literate. Understanding the Nature of Science (NOS) has been regarded as a crucial essence in producing Science literate individuals. Following this, there have been extensive researches worldwide to measure various groups’ conceptions on NOS using instruments developed to cater this need. However, the previous studies in Malaysia only measured the same aspects of NOS while sidelining others, hence limiting the holistic understanding of NOS among Malaysians.